USE OF RANDOM URINE SAMPLES TO ESTIMATE TOTAL URINARY CALCIUM AND PHOSPHATE EXCRETION - GOKCE, C; GOKCE, O; BAYDINC, C; ILHAN, N; ALASEHIRLI, E; OZKUCUK, F; ARSLAN, N (Amer Medical Assoc, 1991)
Calcium-to-creatinine and phosphate-to-creatinine ratios in random single-voided urine specimens were compared with 24-hour calcium and phosphate excretions, respectively, in 67 subjects who were selected prospectively to represent a wide range of renal and parathyroid function as well as urinary calcium and phosphate loss. Simple linear regression analysis revealed significant correlation between the spot urine calcium-to-creatinine ratio and 24-hour total calcium excretion and between the spot urine phosphate-to-creatinine ratio and 24-hour phosphate excretion. Calculating these simple ratios permits easy, rapid, correct, and inexpensive estimation of the daily urinary calcium and phosphate excretion.
Keywords: To-Creatinine Ratio; Quantitative Proteinuria